Recent progress on the role of GABAergic neurotransmission in the pathogenesis of Alzheimer’s disease - Abbas, G.; Mahmood, W.; Kabir, N. (De Gruyter, 2016)
Despite their possible causative role, targeting amyloidosis, tau phosphorylation, acetylcholine esterase, glutamate, oxidative stress and mitochondrial metabolism have not yet led to the development of drugs to cure Alzheimer's disease (AD). Recent preclinical and clinical reports exhibit a surge in interest in the role of GABAergic neurotransmission in the pathogenesis of AD. The interaction among GABAergic signaling, amyloid-β and acetylcholine is shown to affect the homeostasis between excitation (glutamate) and inhibition (GABA) in the brain. As a consequence, over-excitation leads to neurodegeneration (excitotoxicity) and impairment in the higher level functions. Previously, the glutamate arm of this balance received the most attention. Recent literature suggests that over-excitation is primarily mediated by dysfunctional GABA signaling and can possibly be restored by rectifying anomalous metabolism observed in the GABAergic neurons during AD. Additionally, neurogenesis and synaptogenesis have also been linked with GABAergic signaling. This association may provide a basis for the needed repair mechanism. Furthermore, several preclinical interventional studies revealed that targeting various GABA receptor subtypes holds potential in overcoming the memory deficits associated with AD. In conclusion, the recent scientific literature suggests that GABAergic signaling presents itself as a promising target for anti-AD drug development.